Creative thinking: A systematic review of the literature of the last five years - Sanmartin Orbe, Gerardo Alfonso (2025)
Objective: This research aims to analyze the integration of creative thinking in educational and work environments in the last five years. Theoretical Framework: This systematic review analyzes the integration of creative thinking in educational and work environments, focusing on the pedagogical and methodological strategies that have been shown to be effective in the development of this skill. Through the review of recent studies, innovative approaches that encourage creativity in students are identified, such as the use of audiobooks, artistic projects and active methodologies such as design thinking. Method: The PRISMA method was used to ensure a rigorous approach to data selection. An exhaustive search was carried out in databases such as Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex and the César Vallejo University, which made it possible to compile relevant studies published in the last five years. Results and Discussion: The results of the systematic review indicate that the development of creative thinking is essential in educational and work environments, highlighting the need to implement innovative pedagogical strategies. The inclusion of active methodologies, such as design thinking and the use of audiobooks, are crucial to foster creative skills in students, preparing them to face real challenges in a constantly changing world. Implications of the Research: The integration of creative thinking in educational and work environments is essential to prepare students for the challenges of today's world. Originality/Value: Generate a comprehensive approach to creative thinking, through the analysis of various pedagogical strategies and their impact in educational and work environments.